Canola oil as an alternative quenchant for the AISI 8640 steel - Deo, Leonardo Pratavieira; Malafaia, Artur Mariano de Sousa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
AISI 8640 is one of the most used steel in the manufacturing industry due its wide range of applicability and properties. The quenching process is commonly applied in parts made of this steel in order to enhance some properties, such as strength and hardness. Petroleum derived oils are the most common quenchants, however this kind of quenchant is considered to be non-biodegradable, toxic to the health and environment, as well as, not renewable. In the present study, canola oil presented the same efficiency than a conventional petroleum derived oil in the quenching process of AISI 8640 steel billets with diameter of 25.4mm.